Acute hepatitis of unknown origin in Europe—Adding fuel to already burning pandemic. (September 2022) - Tahir, Maliha; Lund, Sejal; Hamdana, Amatul Hadi; Ahmad, Shahzaib; Umar, Muhammad; Farid, Shahzaib; Siddiqui, Muhammad Osama; Khawar, Muhammad Muneeb
Abstract: The rise in the cases of acute hepatitis of unknown aetiology in the paediatric population is a public health concern worldwide and investigations to ascertain the exact cause of this outbreak are being carried out extensively by the concerned authorities. In early April 2022, the World Health Organisation (WHO) issued a warning on acute hepatitis of unknown origin in children. Since then, there have been continuing additional reports of the cases globally. The recent cases of acute hepatitis of unknown aetiology are more prevalent in children aged <10 years, are more clinically severe, and a high percentage of infected individuals develop acute liver failure in contrast to the previous cases. The aetiology of this disease and its complete pathogenesis is still unclear. This review critically focuses on the current leading hypothesis and provides comprehensive information regarding this recent outbreak that can help in handling the situation by a better understanding of its aetiology. Highlights: Various cases of acute hepatitis of unknown origin have been reported to WHO from different countries. Most of the cases reported were of the children from one month to 16 years and majority of them were infected with adenovirus. The diseases is challenging due to its unknown aetiology, insufficient data to establish management plans and its severity. International health organizations have teamed up and set up surveillance systems and investigations to help identify the aetiology. WHO and CDC have recommended general preventive measures including hand and respiratory hygiene.